Ответ:
Пошаговое объяснение:
9x-8=7x+2
9х-7х=8+2
2х=10
х=5
11(-x+3)=-5(2x+4)
-11х+33=-10х-20
-11х+10х=-33-20
-х=-53
х=53
9х-7х=2+8
х=10:2
Ответ: х=5
====
11(-x+3)= -5(2x+4)
-11х+33= -10х-20
-11х+10х= -20-33
-х= -53
х= -53:(-1)
Ответ: х=53
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
9x-8=7x+2
9х-7х=8+2
2х=10
х=5
11(-x+3)=-5(2x+4)
-11х+33=-10х-20
-11х+10х=-33-20
-х=-53
х=53
9x-8=7x+2
9х-7х=2+8
2х=10
х=10:2
х=5
Ответ: х=5
====
11(-x+3)= -5(2x+4)
-11х+33= -10х-20
-11х+10х= -20-33
-х= -53
х= -53:(-1)
х=53
Ответ: х=53